Development and nutritional evaluation of pomegranate peel enriched bars. - Rameeza Abbas; Muhammad Aamir; Farhan Saeed; Amar Shankar; Jaspreet Kaur; Rutaba Nadeem; Ashish Singh Chauhan; Ali Imran; Muhammad Afzaal; Abdela Befa Kinki (PLoS ONE)
Pomegranate peel powder is used as a functional ingredient in the development of nutritional bars. Pomegranate (Punica granatum) is well known fruit belongs to punicaceae family having multiple health benefits, not only limited to its edible parts but also in its non-edible parts mostly the peel. Fruit wastes are rich source of nutrients, and can be used for the development of functional food products. Pomegranate peel is considered to be beneficial due to its functional and therapeutic properties as it is a source of many biological active components like polyphenols, tannins and flavonoids. Nutrient rich and ready-made foods are the demand of everyone due to their easy availability and cost effectiveness. Among the confectionary products, bars are liked by individuals of different age groups. Hence, nutritional properties of bars can be enhanced by using pomegranate peel powder. The current study was designed to develop bars enriched with pomegranate peel powder as a basic ingredient. Pomegranate peel powder is prepared and analyzed for proximate, mineral, total phenolic content, total flavonoid content and anti-oxidant potential (DPPH). By using pomegranate peel powder, oats and jaggery, bars were prepared. In this research, five treatments T0 (0% pomegranate peel powder and 100% oats). T1 (5% pomegranate peel powder and 95% oats), T2 (10% pomegranate peel powder and 90% oats), T3 (15% pomegranate peel powder and 85% oats) and T4 (20% pomegranate peel powder and 80% oats) were used. The developed product is analyzed for proximate, mineral, total flavonoid contents, total phenolic content and anti-oxidant potential (DPPH). Proximate analysis of bars revealed that moisture, protein, fat, fiber, ash and nitrogen free extract ranges from T0 to T4 (13.38±1.21 to 11.32±1.15, 9.56±0.92 to 8.32±1.14, 9.05±1.21 to 7.93±1.08, 5.23±0.82 to 16.89±0.64, 2.05±0.87 to 2.92±1.25 and 62.51±0.85 to 52.62±0.93 respectively. Phytochemical analysis of bars enriched with pomegranate peel powder revealed that total phenolic content, total flavonoid content and antioxidant potential of bars ranges from T0 to T4 (142.74±0.65 to 211.79±0.63 mg GAE/100g, 129.16±0.64 to 192±0.53 mg QE/100g and 41.35±0.82 to 64.57±0.69%) respectively. Mineral analysis of bars enriched with pomegranate peel powder revealed that calcium, Phosphorus, Potassium, Iron, Magnesium content ranged from T0 to T4 (25.42±0.63 to 31.06±0.58, 51.00±1.01 to 45.05±1.09, 59.46±1.13 to 79.15±0.28, 1.32±1.20 to 1.95±0.83 and 54.17±0.88±0.58 to 57.36±0.68 mg/100g respectively). Sensory evaluation is done for color, aroma, taste, texture overall acceptability. T3 got maximum score. Then, the data obtained were evaluated by CRD design. On the basis of results revealed that treatment T3 with 15% pomegranate peel powder was overall highly acceptable.